Effectiveness, adherence and safety of evolocumab in a Swiss multicenter prospective observational study. (14th October 2021) - Nanchen, D; Carballo, D; Reichert, N; Sudano, I
Abstract: Background/Introduction: Achievement of low LDL-C-levels and adherence to lipid lowering therapy (LLT) is essential to prevent recurrent cardiovascular (CV) events. However, most patients (pts) with acute coronary syndromes don't maintain LDL-C levels within guideline recommendations beyond 1 year. Practical solutions to increase long-term adherence to LLT are needed. Purpose: To describe pts receiving evolocumab (evo) and drug adherence in a real-world clinical setting. Methods: We enrolled adults ≥18 years with confirmed atherosclerotic cardiovascular disease (ASCVD) or at high CV risk, and elevated LDL-C levels despite maximally tolerated statin therapy. Physicians in clinical practice prescribed evo according to Swiss reimbursement limitations. At baseline (BL), all pts used evo; some were already on PCSK9i treatment (PCSK9i pre-treated), others were newly initiated on evo (PCSK9i naïve); planned follow-up was 12 months. The web-based mHealthAlert system was offered to support pts' therapy management. The primary outcome was cholesterol levels at BL and after 3, 6 and 12 months of evo therapy. Results: All 100 enrolled pts completed 12 months follow-up. For BL characteristics see Table. 81% had a history of at least one CV event and 55% had ≥2 previous CV events; 3% had familial hypercholesterolemia. At BL, 71% had a history of statin-related muscle symptoms, 44% had documented statin use, 65% were PCSK9i pre-treated and 35% were PCSK9i naïve; overall median LDL-C was 1.9 mmol/L. In PCSK9i naive pts, median LDL-C at enrolment was 3.5 mmol/L and fell by a mean of 2.1 mmol/L (60% reduction) within 3 months of evo initiation; this reduction was maintained over 12 months. The 2016 ESC/EAS LDL-C goals (<1.8 mmol/L) were attained at least once over 12 months by 74% of pts while 69% attained the 2019 goals (<1.4 mmol/L). In PCSK9i pre-treated pts, LDL-C remained stable during evo treatment; 79% and 74% attained the 2016 and 2019 goals, respectively, at least once over 12 months. Goal attainment was higher in pts receiving combination therapy of evo ± statin ± ezetimibe (Figure). Overall, 89% of pts self-reported full adherence to evo. Adverse events were reported in 30% of pts, two events in one pt were considered serious (increased blood creatine phosphokinase and myopathy) and three pts discontinued evo due to adverse events. Conclusion: In Swiss clinical practice, evo was mainly used in high CV risk pts with statin-related muscle symptoms and severe CV disease. In this population, adherence to evo and low LDL-C levels were maintained over one-year. Among pts using evo either in mono- or combination therapy, the majority attained guideline recommended LDL-C levels. However, goal attainment was higher in pts using evo in combination with other LLT, especially with regards to LDL-C <1.4 mmol/L. Effectiveness and safety of evo in real-world clinical practice was comparable to that found in randomized, controlled clinical trials. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Study 20150245 was funded by Amgen Switzerland AG